Results of the Emergency Medical Service Systems Development at Charoensin Hospital, Charoensin District, Sakon Nakhon Province - โชคคติวัฒน์ สัจพงษ์ (Medical Journal of Sakon Nakhon Hospital, 2024)
This quasi–experimental research aimed to study the outcome of the emergency medical service (EMS) systems development at Charoensin hospital. One hundred and one subjects were selected with the purposive sampling technique. Those were 54 emergency rescuers, 8 ambulance drivers, 13 patient helpers and stretchers, 26 nurses and emergency medical technician. The development was carried out according to the quality cycle theory process (Deming cycle: PDCA) from January to April, 2023. Data were analyzed using the descriptive statistics; number, mean, percentage and standard deviation and inferential statistics; paired sample t–test. The qualitative data was summarized according to the changed process. The results revealed that in the planning stage, opinions were mobilized from many sectors. The potential development plan for emergency accident officers, developing operational units and guideLines for operating leading to the implementation of the plan were generated. In the inspection stage, there was continuous monitoring and supervision. The work processes were adjusted as the followings 1) Increased ambulance drivers for 24 hours a day 2) Arranged daily EMS nurses to work separately from accident and emergency room 3) Organized a monthly review meeting when an incident occurs 4) Renovated the accident emergency room 5) Set up the service guideLines 6) Installed the GPS system, camera tracking and speed record of EMS vehicles 7) Organized the training in pre–hospital patient care and practice plans for mass accidents and disasters. The potential development of emergency accident officers in knowledge, skills, and attitudes aspects showed that after development, all groups had a good level of knowledge and attitude which were significantly different from those before development (p < 0.001). However, the attitudes of the emergency responders before and after development were not statistically different. The skills of emergency accident officers were at the good level which was statistically different from those before development (p < 0.05). As a result, the critical or urgent emergency patients were rescued and delivered by a more comprehensive emergency medical service system.